(untitled) (Research, Society and Development, 2021)
Objective: The aim of the present study to assess the association between the prevalence of probable bruxism and orofacial factors in children three to nine years of age. Material and Methods: A cross-sectional study was conducted with 120 children who sought treatment at the paediatric dental clinic of the Metropolitan University of Santos in 2017. The guardians filled out a questionnaire designed using the criteria of the American Association of Sleep Medicine for the diagnosis of bruxism. The participants were also submitted to a clinical examination for the evaluation of malocclusion. Results: The obtained results were computed and statistical analysis was carried out adopting a level of significance of 95%. Results: The prevalence of bruxism among the children was 39,2%; 17.5% in the primary dentition and 21.6% in the mixed dentition. The analysis revealed that bruxism was associated with headache (OR=2.63; 95 CI:1.1-5.8) and open bite (OR=3.23; 95CI:1.16-8.94). Conclusion: There is a strong association between bruxism and headache, and bruxism and open bite in children.